Politik Identitas Etnis Kedang Pada Pemilihan Kepala Daerah Kabupaten Lembata 2017 - Gabriel Durah Langoday (CV. Era Digital Nusantara, 2023)
Abstract: This article examines how political decentralization in the 2017 regional elections has shaped the phenomenon of the use of identity politics that successfully won the SUNDAY pair (Eliaser Yentji Sunur and Thomas Ola Langoday) in the implementation of the 2017 regional elections in Lembata Regency. Local political dynamics that are still influenced by primodial sentiments have become a factor that fertilizes the use of identity politics in local politics. The 2017 elections in Lembata Regency were followed by five pairs of candidates with the victory of the SUNDAY pair in two sub-districts with a total vote of 70%, showing how the issue of identity politics played can increase the votes of candidates for Regent and Vice Regent in the implementation of the elections. Purpose: The purpose of this article is to see how the issue of identity politics was formed by SUNDAY pair in gaining support from ethnic kedang in the 2017 regional election. Design/Methodology/Approach: This research uses a descriptive qualitative approach by attempting to explain how identity issues were formed and raised as an effort to win the SUNDAY pair. Determination of Informants using snowball technique starting from key informants, Various information that will be obtained from key informants will be used as reference material in determining other informants.. Findings: The results showed that the victory of the SUNDAY pair was inseparable from its ability to determine the segmentation of voters who were more dominantly interested in various issues of identity politics. Identity issues were used to gain support from the Kedang community located in two sub-districts, namely Omesuri and Buyasuri, displayed in the form of using local languages in various campaign activities and raising the social conditions of the Kedang community through folklore that has grown in the community, thus succeeding in creating a voting power group between the Lamaholot and Kedang ethnicities. Originality/Value: This research is more focused on the use of Kedang ethnic identity politics in winning Sunday pairs in the 2017 regional elections Keywords: Identity Politics, Kedang, Lembata, Pilkada